Rice Galaxy: an open resource for plant science published - CGIAR Research Program on Rice (2019)
Rice Galaxy (http://galaxy.irri.org) is a publicly available website for bioinformatic analyses using 3000 rice genomes sequenced from IRRI's rice genbank (3KRG project, https://gigascience.biomedcentral.com/articles/10.1186/2047-217X-3-7), Antenna Panel (rice genotypes that act as sensors for environmental changes, https://agritrop.cirad.fr/590501/) and other specialized datasets. Tools are available from the galaxy tool shed (http://galaxy toolshed.excellenceinbreeding.org) including for designing single-nucleotide polymorphism assays, analyzing genome-wide association studies, population diversity, rice−bacterial pathogen diagnostics, and a suite of published genomic prediction methods.